First Aid Training for Elementary School Teachers at SD Genta Saraswati Gianyar (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
SD Genta Saraswati is a private elementary school located in the center of Gianyar City. Based on initial interviews, it was stated that teachers encountered many student conditions that required immediate treatment, such as sprains, wounds, stomach aches, fevers, nosebleeds, and other conditions. For this condition, teachers have provided simple treatment, but there is still minimal understanding and skills in providing first aid for children's accidents at school. The aim of this community service activity is to empower partners in providing first aid for children's accidents at school. The method of implementing the program is carried out through socialization, training, assistance with first aid equipment, mentoring, and evaluation of activity results by fully involving partners. This program involved 16 participants, consisting of teachers and staff at SD Genta Saraswati. After delivering the program, participants' knowledge increased, which can be seen from the increase in the average pre-test score from 6.56 to 9.06 (p